The Effect of Green Tea as an Adjuvant to Enzyme Replacement Therapy on Oxidative Stress in Fabry Disease: A Pilot Study - Bertoldi, Giovanni; Carraro, Gianni; Ravarotto, Verdiana; Di Vico, Valentina; Baldini Anastasio, Paola; Vitturi, Nicola; Francini, Francesco; Stefanelli, Lucia Federica; Calò, Lorenzo A. (Frontiers in Nutrition, 2022)
Enzymatic replacement therapy (ERT) is not very effective in halting the progression of Fabry disease (FD) toward cardiovascular (CV)-renal remodeling, particularly in case of late diagnosis. FD patients have increased oxidative stress (OS), critical for the induction of CV-renal remodeling. We investigated the effects of an adjuvant antioxidant treatment to ERT on OS and the possible advantages for related complications. OS was evaluated in 10 patients with FD before ERT, after 12 months of ERT, and after 6 months of adjuvant green tea (GT) to ERT by the following experiments: expression of p22phox; phosphorylation state of MYPT-1 and ERK 1/2 (by western blotting); and quantification of malondialdehyde (MDA) and heme oxygenase (HO)-1 levels (by ELISA). p22phox and MYPT-1 phosphorylation decreased after ERT and significantly further decreased after GT. ERK 1/2 phosphorylation and MDA levels remained unchanged after ERT, but significantly decreased after GT. HO-1 significantly increased after ERT and further increased after GT. This study provides preliminary data highlighting the antioxidant effect exerted by ERT itself, further amplified by the adjuvant antioxidant treatment with GT. The results of this study provide evidence of the positive effect of early additive antioxidant treatment to reduce OS and prevent/alleviate cardio and cerebrovascular-renal complications related to OS.